Where do "Soccer Moms" Come From? : Cognitive Constraints on Noun-Noun Compounding in English - Keane, Mark T.; Costello, Fintan (Trinity College Dublin, Department of Computer Science, 1996)
Every year new noun-noun combinations enter the English language and become common parlance; compounds like "notebook computer" and "soccer mom". But, why is one pair of words chosen rather than another pair ? For example,why do we not use "patio-tile computer" and "sports mother" ? Clearly, many factors influence the process. We concentrate on the cognitive factor of informativeness; namely, that a novel combination should convey its meaning unambiguously. Costello & Keane (1996) have shown that some classes of concept promote ambiguity (or polysemy) in novel nounnoun compounds; artifact and superordinate terms promote polysemy whereas natural-kind and basic-level terms do not. Here we show that the topology of these conceptual classes in a large corpus of familiar compounds indicates that they constrain the compounds that appear in a language.
Keywords: Computer Science